O ministério público e as provas digitais: conformidade com a LGPD e a garantia de direitos fundamentais - Pereira, José de Lima Ramos (2024)
The present thesis addresses and analyzes the performance of the Public Prosecutor's Office facing the challenges arising from the technological (r)evolution, with special emphasis on its compliance with the rules and principles established in Law No. 13,709/2018, also known as the General Personal Data Protection Law (LGPD), as well as in the context of digital evidence. The general objective of this research is to analyze, through the understanding of the legal framework for personal data protection and the characteristics and peculiarities of digital evidence, the adaptation and compliance of the Public Prosecutor's Office with the precepts and axioms established by the LGPD. The methodology adopted is of a bibliographic and documentary nature, based on the deductive method. It is possible to verify that the Public Prosecutor's Office has significantly evolved in implementing the General Personal Data Protection Law (LGPD), both from a finalistic and administrative perspective, and such evolution is essential for the effective performance of its constitutional role as a defender of legal order, democratic regime, and social and individual interests that cannot be waived in a context marked by the increasing digitization and virtualization of political, legal, and social relations, and the intensive use of personal data.